2015
DOI: 10.1128/ec.00268-14
|View full text |Cite
|
Sign up to set email alerts
|

The Anillin-Related Region of Bud4 Is the Major Functional Determinant for Bud4's Function in Septin Organization during Bud Growth and Axial Bud Site Selection in Budding Yeast

Abstract: bThe anillin-related protein Bud4 of Saccharomyces cerevisiae is required for axial bud site selection by linking the axial landmark to the septins, which localize at the mother bud neck. Recent studies indicate that Bud4 plays a role in septin organization during cytokinesis. Here we show that Bud4 is also involved in septin organization during bud growth prior to cytokinesis, as bud4⌬ shs1⌬ cells displayed an elongated bud morphology and defective septin organization at 18°C. Bud4 overexpression also affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 49 publications
1
36
0
4
Order By: Relevance
“…(2010) and confirmed here, both Gin4 and Kcc4 have functional KA1 domains at their extreme C-termini, and it has been shown that Gin4 contributes to regulating the lipid distribution in the inner leaflet of the PM in a way that affects the efficiency of cytokinesis ( Roelants et al ., 2015 ). Similarly, the septin-binding proteins Bud4 ( Kang et al ., 2013 ; Wu et al ., 2015 ) and Boi1 (and its paralogue Boi2; Hallett et al ., 2002 ), which are necessary for proper septin organization for bud emergence, have phosphoinositide-binding pleckstrin homology domains at their extreme C-termini ( Yu et al ., 2004 ), and PtdIns4,5P 2 is another lipid that appears to be enriched at the bud neck ( Garrenton et al ., 2010 ). Moreover, septin filament assembly is robustly stimulated in vitro by the presence of PtdIns4,5P 2 in membranes ( Bertin et al ., 2010 ; Bridges et al ., 2014 ); in the cell, the septin filaments in the collar are tightly apposed to the PM at the bud neck, and this association is required for their function ( Bezanilla et al ., 2015 ; Finnigan et al ., 2015b ).…”
Section: Discussionmentioning
confidence: 99%
“…(2010) and confirmed here, both Gin4 and Kcc4 have functional KA1 domains at their extreme C-termini, and it has been shown that Gin4 contributes to regulating the lipid distribution in the inner leaflet of the PM in a way that affects the efficiency of cytokinesis ( Roelants et al ., 2015 ). Similarly, the septin-binding proteins Bud4 ( Kang et al ., 2013 ; Wu et al ., 2015 ) and Boi1 (and its paralogue Boi2; Hallett et al ., 2002 ), which are necessary for proper septin organization for bud emergence, have phosphoinositide-binding pleckstrin homology domains at their extreme C-termini ( Yu et al ., 2004 ), and PtdIns4,5P 2 is another lipid that appears to be enriched at the bud neck ( Garrenton et al ., 2010 ). Moreover, septin filament assembly is robustly stimulated in vitro by the presence of PtdIns4,5P 2 in membranes ( Bertin et al ., 2010 ; Bridges et al ., 2014 ); in the cell, the septin filaments in the collar are tightly apposed to the PM at the bud neck, and this association is required for their function ( Bezanilla et al ., 2015 ; Finnigan et al ., 2015b ).…”
Section: Discussionmentioning
confidence: 99%
“…At cytokinesis, septins split into a double ring, so the mother and the daughter cells each inherit one half of the original septin ring. These septin rings then act as a scaffold for landmark proteins such as Bud4, a fungal anillin-like protein (65, 66, 99, 125). The association between Bud4 and septins is not as straightforward as septins simply tethering Bud4, but instead there is clearly a conserved reciprocal relationship.…”
Section: How Septins Pattern and Shape Cellsmentioning
confidence: 99%
“…The association between Bud4 and septins is not as straightforward as septins simply tethering Bud4, but instead there is clearly a conserved reciprocal relationship. In S. cerevisiae , Bud4 is required for normal septin organization and the splitting of the septin ring; the very process Bud4 itself relies on for segregation to each cell after division (32, 65, 66, 99, 123, 125). The synergistic links between Bud4 and septins are conserved across a variety of fungi including S. pombe , where the Bud4 homolog, Mid2 acts to stabilize the septin rings during cytokinesis similar to that in budding yeast (6).…”
Section: How Septins Pattern and Shape Cellsmentioning
confidence: 99%
“…; Wu et al . ). In the filamentous fungus Neurospora crassa , the Bud4 homologue is required for the process of septum formation by interacting with the Rho family small GTPases (Justa‐Schuch et al .…”
Section: Introductionmentioning
confidence: 97%
“…BUD4 is one of them. This gene product controls bud site selection by interacting with the bud neck filaments consisted of septin in the budding yeast Saccharomyces cerevisiae (Sanders & Herskowitz 1996;Gladfelter et al 2005;Wu et al 2015). In the filamentous fungus Neurospora crassa, the Bud4 homologue is required for the process of septum formation by interacting with the Rho family small GTPases (Justa-Schuch et al 2010;Delgado-Alvarez et al 2014).…”
Section: Introductionmentioning
confidence: 99%